Back Cover: Comprehensive Profiling of Lysine Acetylome in Baculovirus Infected Silkworm (Bombyx mori) Cells. Issue 1 (15th January 2018) - Hu, Dongbing; Xue, Shengjie; Zhao, Cui; Wei, Ming; Yan, Huihui; Quan, Yanping; Yu, Wei
Abstract : DOI:10.1002/pmic.201700133 Bombyx mori nucleopolyhedrovirus and Bombyx mori are important natural biological models for studying host‐pathogen interactions. In article number 1700133, Dongbing Hu et al. applied an integrated proteomics approach including TMT labeling, HPLC fractionation, and LC‐MS/MS to quantify acetylome of BmN cells infected with BmNPV. BmNPV infection may globally impact host acetylome involving in energy metabolism, macromolecular synthesis and metabolism, gene expression and transport of substances.